Surprise me! On the impact of unexpected benefits on other-praising gratitude expressions. Issue 8 (16th November 2020) - Weiss, Alexa; Burgmer, Pascal; Lange, Jens
ABSTRACT: Gratitude reinforces social bonds. This relationship-regulating function depends on whether and how it is expressed. People can express gratitude in different ways: Beneficiaries may emphasise how they profited from a benefit (self-benefiting) or focus on the benefactor's actions and characteristics related to it (other-praising). What underlies these expressive styles remains unclear. Based on findings that other-praising gratitude expressions have unique positive effects on interpersonal relationships, four studies ( N  = 1, 188) investigated a novel antecedent of these expressions: unexpectedness of the benefit. In Study 1, we content-coded participants' thank-you notes for an actual Christmas present. Path modelling revealed that unexpectedness of the benefit predicted other-praising, whereas happiness with the present predicted self-benefiting. These results were robust to relevant covariates and mirrored by participants' self-reported self-benefiting and other-praising intentions. Studies 2–4 (preregistered) investigated samples from two different populations and experimentally manipulated (un)expectedness of recalled or imagined benefits. Given mixed experimental results, we conducted an internal meta-analysis. Across experimental studies, unexpected benefits increased other-praising, albeit weakly so, but not self-benefiting. In addition, the effect of unexpectedness on other-praising was significantly different from that on self-benefiting. We discuss potential processes and moderators of the effect of unexpected benefits on gratitude expressions.